(untitled) (Canadian Oncology Today, 2024)
Prostate cancer is among the most prevalent malignant conditions globally, and both incidence and mortality are expected to increase markedly over the next two decades. Recently, the diagnostic and treatment landscape for managing this disease underwent remarkable advances that led to the incorporation of innovative approaches, such as prostate-specific membrane antigen (PSMA) theranostics. PSMA, which is also known as folate hydroxylase or glutamate carboxypeptidase, is a transmembrane protein 100- to 1000-fold overexpressed by prostate cancer cells compared to healthy cells found in the benign prostate gland, salivary glands, proximal renal tubules, small intestine mucosa, and hepatocytes, amongst others. Since its discovery over 30 years ago (see Figure 1 for this and other milestones), PSMA has caught the attention of the scientific community as a potential therapeutic target, and for the past two decades many efforts have been undertaken to identify and develop PSMA ligands and antibodies that could be exploited as prostate cancer therapeutics. This review aims to provide an overview of available PSMA ligands, their mechanisms of action, diagnostic and therapeutic applications, and future perspectives of PSMA-targeted therapeutic approaches within the field of radioligand therapy (RLT).